RANCANG BANGUN SISTEM INVENTORI BARANG PADA VENDOR DOKUMENTASI FILMYLAB JAYAPURA - Fajar Sura Alfaruq; Emy L. Tatuhey (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
FilmyLab Jayapura is a documentation service company that relies on equipment such as cameras and visual equipment. The absence of an inventory recording system causes frequent losses and irregularities in the use of equipment. This study aims to develop a web-based inventory information system to record borrowing and returning activities in real-time. The system is built using the Waterfall method through the stages of analysis, design (ERD and diagrams), implementation using PHP Laravel and MySQL, and blackbox testing. The implementation results show that the system is able to increase efficiency, transparency, and facilitate inventory monitoring through data management features, transactions, and visual reports